Poly (vinylidene fluoride) (PVDF) membranes for pervaporation of butanol/water mixture: fabrication, characterization and application - Nurul Izzati Ab Rahim (School of Bioprocess Engineering, 2017)
This research is focus on the preparation of polymeric membrane and functionalized this membrane using ionic liquid by studying the effects of certain parameters. To produce the optimum polymeric membrane, the formation of finger-like structure needs to be increased by manipulating two major parameters, the coagulation bath medium and evaporation time during phase inversion. These techniques will influence the membrane structure formation allowing higher ionic liquid uptake during the impregnation process. In this research, the performance of the membrane is investigated using the pervaporation technique by separating the mixture of butanol/water.